ASSESSING THE WTO COMPLIANCE OF SELECTED ASPECTS OF SOUTH AFRICA’S INTERNATIONAL TRADE ADMINISTRATION AMENDMENT BILL - Lonias Ndlovu (Obiter, 2021)
This article argues that while South Africa’s International Trade Administration Amendment Bill and the attendant proposed regulations may generally be regarded as a positive legislative intervention, to a large extent, the new regulatory regime goes against the spirit, object and purport of the World Trade Organization (WTO) anti-dumping agreement and is even in conflict with South Africa’s International Trade Administration Act itself. In order to substantiate the above reservations, this article first outlines the basics of WTO dumping and anti-dumping law before proceeding to point out aspects of South Africa’s anti-dumping law and practicewhich incorporate WTO tenets. With the aid of selected WTO disputes and examples from comparative WTO member states, this article also comments on selected impugned changes likely to be introduced by the Bill and the new regulations and concludes that the proposed new law is unlikely to be WTO compliant. This conclusion is premised on the fact that South African dumping and anti-dumping law relating to confidentiality, the process of conducting investigations, termination of investigations based on de minimis margins and interested party hearings does not always mimic the legal position as espoused in the WTO anti-dumping agreementand interpreted in selected WTO disputes.